Reconstruction of the Sanction System in the Indonesian National Police Professional Ethics Code to Achieve Proportionality of Penalties for Position Violations and Abuse of Authority - Ramadhan Nasution; Bambang Soesatyo (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study analyzes the problems in imposing sanctions under the Indonesian National Police Professional Ethics Code (KEPP) and reconstructs a sanction system based on the principle of proportionality to ensure legal certainty, justice, and institutional accountability. Key issues include disparities in KKEP decisions, subjectivity of ethics panels, the absence of objective parameters for assessing misconduct, and overlaps between ethical, disciplinary, and criminal regimes that create legal uncertainty and the risk of double punishment. Using a normative juridical method with legislative and conceptual approaches, this study examines Law Number 2 of 2002, Government Regulation Number 1 of 2003, and Police Regulation Number 7 of 2022. The findings show that the current KEPP sanction system lacks measurable and uniform standards, resulting in disproportionate sanctions. This study proposes legal reforms through revised sanction norms, a score-based grading system, ethical sentencing guidelines, integrated SOPs, and a national ethical jurisprudence database. These measures are expected to promote a more objective, consistent, and substantively just sanction system.